How to ‘deconvolute’ lung evolution - vertebrate ontogeny - the ‘short history’ of evolution - Torday, John S. (Henry Stewart Talks, 2016)
Ontogeny, the ‘short history’ of the organism, Embryogenesis, blastula to gastrula, Molecular signaling and morphogenesis, Alternating extrinsic/intrinsic selection pressure, Swim Bladder-Lung homology, Continuum from ontogeny to phylogeny, homeostasis, repair, PTHrP necessary for alveolarization, PTHrP, Glucocorticoid and βAdrenergic Receptor gene duplications, Evolution of Endothermy